2023
DOI: 10.3389/fmicb.2022.1076675
|View full text |Cite
|
Sign up to set email alerts
|

Metabolome and microbiome analysis revealed the effect mechanism of different feeding modes on the meat quality of Black Tibetan sheep

Abstract: IntroductionBlack Tibetan sheep is one of the primitive sheep breeds in China that is famous for its great eating quality and nutrient value but with little attention to the relationship between feeding regimes and rumen metabolome along with its impact on the muscle metabolism and meat quality.MethodsThis study applies metabolomics-based analyses of muscles and 16S rDNA-based sequencing of rumen fluid to examine how feeding regimes influence the composition of rumen microbiota, muscle metabolism and ultimatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 74 publications
3
20
0
Order By: Relevance
“…The present research indicates a significant positive correlation between the molar proportion of acetate and the relative abundance of the Rikenellaceae RC9 gut group , with negative correlations observed for propionate and total VFA. This finding is consistent with previous studies, which reported a negative correlation between the RC9 gut group and propionate ( Li et al, 2022 ; Zhang et al, 2023 ). The negative correlation could be attributed to the production of acetate by some members of the RC9 gut group , as reported by Su et al (2014) .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The present research indicates a significant positive correlation between the molar proportion of acetate and the relative abundance of the Rikenellaceae RC9 gut group , with negative correlations observed for propionate and total VFA. This finding is consistent with previous studies, which reported a negative correlation between the RC9 gut group and propionate ( Li et al, 2022 ; Zhang et al, 2023 ). The negative correlation could be attributed to the production of acetate by some members of the RC9 gut group , as reported by Su et al (2014) .…”
Section: Discussionsupporting
confidence: 94%
“…The RC9 gut group is crucial for fiber digestion, rumen fermentation pattern, and epithelial development ( Qiu et al, 2022 ). However, other studies have indicated that it may have a negative impact on the enhancement of ruminal N utilization efficiency ( Zhang et al, 2023 ). Our study revealed that the 400 g/d FAF supplementation group had a significantly lower abundance of the Rikenellaceae RC9 gut group than the other groups, underscoring the importance of this dose in improving nitrogen utilization efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…At the genus level, Prevotella and Treponema emerged as dominant. The presence of pyruvate oxidation genes in Prevotella equips these species to flourish in nutrient-scarce environments, leading to their abundance during the early feed fermentation stages [56,57,62]. Concurrently, Chytridiomycota, Ascomycota, and Mucoromycota were identified as the primary anaerobic fungi phyla in the rumen for different roughages, consistent with findings for cows and goats [63].…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, specific bacteria like Rikenellaceae and Porphyromonadaceae are linked to particular roughage types, influencing the degradation rates of nutritional components [55]. These insights emphasize the integral role of rumen microorganisms in processing roughage to extract essential nutrients for the host animal [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…Carcass quality was measured during the splitting process. In this case, the eye muscle area (EMA), rib fat thickness (GR), abdominal fat thickness (AFT) and backfat thickness (BFT) were measured according to previous methods ( Zhang, Han, Gui, et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%